Reaksi Masyarakat Krucil terhadap Produk Pembiayaan di BMT Cabang Krucil Probolinggo - Norhayati, Norhayati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research issue aims to determine the public’s response to BMT financing products. This research aims to determine the public's response to BMT financing products. This research uses a qualitative approach, data is collected through interviews with the community, as well as several community figures who are considered influential in society. The research results show that people have not used many financing products from BMT. Financing products are not widely used by the public due to a lack of promotion and outreach, as well as the existence of commercial banks which are still the main priority in borrowing money. Thus, efforts are still needed to socialize BMT financing products so that the products are known and used by the public.